Sme Borrower Discourage Analysis In Indonesia And Malaysia: An Impact Analysis On Business Performance - Sumaji, Yoseva Maria Pujirahayu; Whidya Utami, Christina; Bramantyo , Paskalis Dio (Jurnal Locus Penelitian dan Pengabdian, 2025)
Urgency of Research: SMEs in Indonesia and Malaysia are often constrained by capital or finance. The results of the identification showed that application costs, and self-efficacy were the causes of Discourage Borrower (DB). On the other hand, the condition of Dicourage Borrower affects the performance of SMEs in Indonesia and Malaysia. Considering that the findings are still partial, this study seeks to integrate the role of Borrower Discourage and the aspect of efficiency moderation for SME business performance in Indonesia and Malaysia. The purpose of this study is (a) to analyze the determinant of discouraged borrowers, namely application fees, whether it affects the performance of SMEs in Indonesia and Malaysia.( b) to analyze whether the determinant of discouraged borrowers, namely self-efficacy, has an effect on the performance of SMEs in Indonesia and Malaysia. (c) efficiency strengthens the influence of application costs and self-efficacy on the performance of SMEs in Indonesia and Malaysia. Research Methods: The research sample in Indonesia was 146 SMEs and 136 SMEs in Malaysia. The data was processed using SEM PLS. And ANOVA uses SPSS to compare the situation of SMEs in Indonesia and Malaysia. Research findings: are to analyze (1) the determinant of discouraged borrowers, namely application fees, has a significant effect on the performance of SMEs in Indonesia and Malaysia (2) the determinant of discouraged borrowers, namely self-efficacy, does not have a significant effect on the performance of SMEs in Indonesia and Malaysia. (3) efficiency is not significant in strengthening the influence of application fees on the performance of SMEs in Indonesia and Malaysia (4) efficiency strengthens the significant influence of Self-Efficacy on the performance of SMEs in Indonesia and Malaysia (5) Self-efficacy does not have a significant effect on the performance of SMEs in Indonesia and Malaysia (6) Efficiency has a significant effect on the performance of SMEs in Indonesia and Malaysia.( 7) Meanwhile, the comparison between the situation of Indonesia and Malaysia shows that if the borrower discourage is high, high self-efficacy will improve the performance of SMEs in Indonesia and Malaysia (8) While the comparison between the situation of Indonesia and Malaysia shows that the high application cost will be high efficiency so that the performance of SMEs in both Indonesia and Malaysia will be better. (9) Meanwhile, the comparison between the situation of Indonesia and Malaysia shows that when the efficiency is high and the efficiency is high, the performance will be better than the low efficiency. This situation is the same in both Indonesia and Malaysia